Hydramethylnon induces synergistic toxicity of pyrethroid mixtures in human lung epithelial cells - Hye-Jin Jeong; Hye-In Park; Tae-Rim Im; Ju-Hui Im; Seung Min Choi; Chang-Ik Choi; Myungwon Seo; Yong Joo Park (Toxicological Research, 2026)

Leuconostoc mesenteroides TH-ST373 Cell-Free Supernatant Against Multidrug-Resistant Escherichia coli - Gyeong-Seon Yi; Thi Minh Nguyen Trang; Jae-Woo Kim; Jin-woo Choi; Ye-Rim Choi; So-Hee Chun; Qiwen Zheng; Tae-Hoo Yi (Probiotics and Antimicrobial Proteins, 2026)

Development of a neutralization ccombody, synthetic hagfish antibody, for viral hemorrhagic septicemia virus (VHSV) targeting glycoprotein G - Abigail Joy D. Rodelas-Angelia; Mark Rickard N. Angelia; Seung Pyo Jeong; Young Rim Kim; Myoung Gwang Choi; Hyoung Jun Kim; Se Ryun Kwon; Kim D. Thompson; Tae Sung Jung (Fish & Shellfish Immunology, 2026)

Biodegradation of PCL, PBS, and PBAT at low temperatures by Aeromicrobium sp. JJY06: A newly isolated strain for cold-environment plastic cleanup - Geeta Chhetri; Jong-Min Jeon; Gayeon Hwang; Tae-Rim Choi; Yung-Hun Yang; Chang-Jun Cha; Jeong-Jun Yoon (Journal of Hazardous Materials, 2025)

Production and characterization of a biodegradable polymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), using the type II methanotroph, Methylocystis sp. MJC1 - Ok Kyung Lee; Seung Gi Kang; Tae-Rim Choi; Yung-Hun Yang; Eun Yeol Lee (Bioresource Technology, 2023)

Macroalgae as a source of sugar and detoxifier biochar for polyhydroxyalkanoates production by Halomonas sp. YLGW01 under the unsterile condition - Shashi Kant Bhatia; Jeong Hyeon Hwang; Suk Jin Oh; Hyun Jin Kim; Nara Shin; Tae-Rim Choi; Hyun-Joong Kim; Jong-Min Jeon; Jeong-Jun Yoon; Yung-Hun Yang (Bioresource Technology, 2023)

Algal biochar mediated detoxification of plant biomass hydrolysate: Mechanism study and valorization into polyhydroxyalkanoates - Shashi Kant Bhatia; Ranjit Gurav; Do-Hyun Cho; Byungchan Kim; Hee Ju Jung; Su Hyun Kim; Tae-Rim Choi; Hyun-Joong Kim; Yung-Hun Yang (Bioresource Technology, 2023)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.